Analyzing Work Stress in the Government Sector: A Case Study of BAPENDA North Sumatra Using Demand-Control and Coping Theories - Risani, Iklila Dara; Siregar, Nina Siti Salmaniah; Turnip, Kaiman (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study analyzes the factors causing work stress, its impact on employee well-being and productivity, and the coping strategies implemented at the Regional Revenue Agency (Badan Pendapatan Daerah, BAPENDA) of North Sumatra Province. The study used a descriptive qualitative approach to understand the dynamics of work stress and a quantitative approach to measure the prevalence of stress-causing factors. The findings show that work stress arises not only from internal factors, such as high workloads and interpersonal conflicts, but also from structural weaknesses, such as unrealistic targets, delayed payment of allowances, and inadequate workplace facilities. Problem-focused coping strategies, such as work planning and social support, were found to be more effective in reducing long-term stress than emotion-focused strategies, such as relaxation and meditation, which only provide temporary benefits. This study makes a significant contribution to the development of the Demand-Control Model and Coping Theory by highlighting the importance of the interaction between internal and external factors in influencing work stress in the government sector. The combination of qualitative and quantitative approaches offers a comprehensive methodology for understanding this phenomenon. The practical implications of this research include recommendations to improve administrative systems, create supportive work environments, and promote problem-focused coping strategies to enhance employee well-being and sustain organizational productivity.